The Role Of Teachers In Instilling Disciplined Character In Early Childhood 5-6 Years Old At Darussalam Early Childhood Education Center - Siti Nurazizah; Candra Mochamad Surya; Opan Arifudin (Yayasan Azka Hafidz Maulana, 2026)
This research is motivated by the role of teachers as substitutes for parents when children are doing learning activities at school, playing an important role in optimizing children's growth and development, especially in developing and forming the independence of early childhood. This study aims to determine the role of teachers in instilling disciplined characters in early childhood 5-6 years in PAUD Darussalam. The study used a qualitative descriptive method with subjects of children aged 4-5 years and class teachers. Data were obtained through observation, interviews, and documentation, then analyzed with data reduction techniques, data presentation, and drawing conclusions. The results of the study show that teachers as educators with examples of teachers coming early to school and tidying up stationery and classrooms, teachers as facilitators, teachers teach to maintain cleanliness of clothes, teach children to wash their hands to be clean, teach to throw trash in the trash, and teachers as mentors, teachers provide guidance to children by conveying the rules that exist in the school while learning and the rules when playing games.